Correlation analysis between palatal connective tissue acquisition methods and postoperative pain after mucogingival surgery - HU Han, DONG Jiachen, LIAO Yue, ZHANG Huanyu, SONG Zhongchen (Kouqiang yixue, 2025)
Objective To evaluate the impact of different methods of harvesting palatal connective tissue on patients’ postoperative pain at the palatal donor site. Methods A total of 30 patients were included. The control group was de-epithelialized free gingival graft technique group, and the experimental group was the single-incision technique group. The keratinized gingival width of the recipient site, number of vertical incisions, number of teeth, donor site mucosa thickness, graft width, graft length, graft thickness, operation time and amount of anesthetic were recorded. The postoperative quality of life rating scale and visual analog scale were completed and statistical analysiswas performedon the results by SPSS 26.0. Results The postoperative quality of life score of the experimental group was significantly lower than that of the control group, and there was no significant difference in the total VAS score of the donor site. In terms of the total postoperative pain level after mucogingival surgery,the number of vertical incisions and graft thickness were positively correlated with the pain. Palate mucosal thickness was negatively correlated with postoperative pain levels. Conclusion In mucogingival surgery, the degree of postoperative pain in the donor palatal region of the patient is independent of the choice of de-epithelialized free gingival graft technique or single-incision technique to obtain subepithelial connective tissue. The surgeon should also give comprehensive considerationsto the anatomical factors of the patient’s donor site, surgical technical level and experience, and aesthetic requirements when selecting the surgical method.